Protective material for edge sealing and use method of protective material during sample preparation

By using edge sealing protective materials prepared by industrial paraffin and high-density polyethylene, the incision and punching positions of the coating specimens are protected, and the corrosion problems caused by improper protection of the incision and punching positions of the coating steel plates in the corrosion test are solved, and more accurate results of the coating corrosion test are achieved.

CN119505555APending Publication Date: 2025-02-25BAOTOU IRON & STEEL (GROUP) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411409647.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

During the corrosion test of the plated steel plate, due to improper protection of the cut and hole-punching positions, the substrate contacts with the corrosion solution and causes corrosion, affecting the corrosion results of the coating.

Method used

A protective material for edge sealing is used, and by mixing industrial paraffin and high-density polyethylene in a certain proportion, a protective material with a melting point range, hardness and toughness of 80-100°C is formed, and the incisions and hole punching positions of the coating sample are protected.

Benefits of technology

Effectively prevent the incision of the plating sample from contacting the corrosion solution, ensuring that only the plating layer participates in the corrosion reaction, improving the effectiveness of the corrosion test, and the material does not react with acids, alkalis and salts, meeting the requirements of the corrosion test.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505555A_ABST
    Figure CN119505555A_ABST
Patent Text Reader

Abstract

Industrial paraffin and high-density polyethylene are blended according to a certain proportion, so that the melting point range of the protective material is 80-100 DEG C, the protective material has certain hardness and toughness, and the protective material has the characteristic of no reaction with acid, alkali and salt, and meets the requirement of edge sealing protection in a corrosion test. The invention further discloses a use method of the protective material for edge sealing during sample preparation. According to the protection material for edge sealing and the use method of the protection material in the sample preparation process, protection treatment is carried out on the notch part and the punching part of the plating layer sample through the protection material, so that exposed base bodies at the notch part and the punching part of the plating layer sample are effectively protected; and in the solution soaking process, the notch position and the punching position are not in contact with a corrosion solution and do not participate in corrosion reaction, so that the effectiveness of a coating corrosion test is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of corrosion testing of metal materials, and in particular relates to a protective material for edge sealing and a method for using the same during sample preparation, which is used for sample preparation of corrosion testing of coating samples. Background Art

[0002] Metal anti-corrosion work has attracted people's attention. Galvanizing or zinc-aluminum-magnesium coating on the surface of metal materials as an anti-corrosion technology has also been rapidly developed. Coated steel plates have been widely studied and applied to industries such as automobiles, home appliances and photovoltaics. Therefore, higher requirements are also put forward for the detection of corrosion resistance of coatings. In the process of immersion test and periodic immersion corrosion test of coated steel plates, the improper protection of the cut and punching positions of the coated samples causes corrosion in contact with the corrosive solution, which affects the corrosion results of the surface coating. In 7.6 of GB / T19746-2018, the cyclic immersion test of metal and alloy corrosion salt solution, it is only proposed that "if the electroplated or coated sample is to be cut, the cut surface needs to be protected", and no specific method is provided. There is no related patent. Only in the literature, it is mentioned that the cut part of the coating sample is protected by the tape method. I have done relevant experiments, but the effect is not ideal. I have also used cold gel and other methods to protect the cut part of the coating sample, but the effect is not good. For this reason, I invented a protective material through experiments and formed a corresponding sample preparation method. This method has a good protective effect on the cut part of the coating sample and is easy to remove after the test. By inventing a sample preparation method for the corrosion test of the coating sample, the contact between the cut of the coating sample and the corrosive solution can be avoided during the corrosion test, ensuring that only the coating participates in the corrosion reaction during the corrosion test, thereby ensuring the effectiveness of the corrosion test of the coating sample. Summary of the invention

[0003] The object of the present invention is to provide a protective material for edge sealing and a method for using the same during sample preparation, wherein the protective material is used to perform protective treatment on the cutout portion and the punched portion of the coating sample, so that the exposed substrate at the cutout portion and the punched portion of the coating sample is effectively protected, and during the solution immersion process, the cutout portion and the punched portion do not contact the corrosive solution and do not participate in the corrosion reaction, thereby ensuring the effectiveness of the coating corrosion test.

[0004] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0005] The invention discloses an edge sealing protective material, which is prepared by mixing industrial paraffin and high-density polyethylene in a certain proportion, so that the melting point ranges from 80 to 100 DEG C, and the material has certain hardness and toughness. The material has the characteristics of not reacting with acids, alkalis and salts, and meets the requirements of edge sealing protection in corrosion tests.

[0006] Furthermore, by adopting a ratio of 60-70% industrial paraffin + 30-40% high-density polyethylene, the melting point range can be adjusted to 80-100°C, and a heating temperature of 270°C is adopted, which is more conducive to uniform mixing of the two materials. After hot-dip edge sealing, cracks are not likely to occur, causing the edge sealing to fall off, and the corrosion test with respect to temperature requirements is met.

[0007] Furthermore, by using 100% industrial paraffin or a ratio of 80-90% industrial paraffin + 10-20% high-density polyethylene, the effect of hot-dip edge sealing meets the requirements of full immersion experiments at room temperature.

[0008] Furthermore, the protective material can be used for full immersion corrosion test and peripheral immersion corrosion test, meeting the corrosion test requirements within the test temperature range of 20-70°C.

[0009] A method for using a protective material for edge sealing when preparing a sample, specifically comprising the following steps:

[0010] 1). According to the corrosion test requirements, cut the coated steel plate sample into a certain size;

[0011] To facilitate hanging the specimen, punch a hole in the middle of its short side, or punch two holes at equal distances on both sides of the long side at symmetrical positions;

[0012] 2) Use sandpaper to remove the burrs on the punched parts, cut parts and sharp corners of the sample;

[0013] 3). Use alcohol to clean the coating surface of the test sample. You can also refer to the GB / T19746-2018 standard to clean the sample to remove the oil on the coating surface of the sample;

[0014] 4). Before the experiment, measure from the bottom to the top on the outer wall of the flat-bottomed glass dish and mark the Amm position and Bmm position lines, and place the flat-bottomed glass dish on the electric heating plate;

[0015] 5). First, place a small amount of the protective material in a glass dish, turn on the electric heating plate, set the temperature to 270°C, heat it to melt and form a protective liquid, and then gradually add protective material until the liquid level reaches the Amm position;

[0016] 6). Use crucible tongs to clamp the center of the sample. Because the front end of the crucible tongs is hollow near the clamping part, it can avoid contact with the four sides of the sample. Before use, stick a piece of tape on each of the two clamping ends of the front of the crucible tongs to increase the stability of the clamping and avoid scratching the coating.

[0017] 7). First, perform protective treatment on the three unpunched edges of the sample; clamp the center of the sample with a crucible clamp, and immerse one edge of the sample vertically into the protective liquid in the flat-bottomed glass dish for 3-5 seconds. After taking it out, the protective liquid quickly solidifies at the incision to form a flat protective film. The other two edges can be processed in turn; if the thickness of the protective film needs to be increased, this step can be repeated; then protect the punched incision edge. At this time, it is necessary to continue to add protective material until its liquid level reaches the Bmm position. The purpose is to immerse the hole on one side of the sample in the protective liquid, so that the incision position on the punched side and the punched position form a protective film;

[0018] 8). Use pointed tweezers to expand a hole in the protective film at the punching position, leaving a certain protective layer for hanging the rope;

[0019] 9). Check the protective film at the cutout and opening of the specimen. If they are sealed intact, the test can be carried out according to the standard.

[0020] Furthermore, the size of the coated steel plate sample is 30 mm×50 mm×δ thickness.

[0021] Furthermore, the diameter of the holes is φ3 mm.

[0022] Compared with the prior art, the beneficial technical effects of the present invention are:

[0023] 1. Invented a protective material for edge sealing, which is composed of industrial paraffin wax and high-density polyethylene in a certain proportion. Its melting point ranges from 80-100°C, and it has a certain hardness and toughness. The material does not react with acids, alkalis and salts, and can meet the requirements of edge sealing protection in corrosion tests;

[0024] 2. The edge sealing effect is good, the matrix of the cut and punched parts does not participate in the corrosion reaction and has no rust;

[0025] 3. The protective materials are low in cost, simple to use, time-saving and highly operational. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The present invention will be further described below in conjunction with the accompanying drawings.

[0027] Figure 1 is the sample size;

[0028] Figure 2 This is a corrosion immersion test in different pH solutions;

[0029] Figure 3 This is a full immersion corrosion test of edge sealing samples (different pH);

[0030] Figure 4 This is a circumferential immersion corrosion test for edge sealing specimens;

[0031] Figure 5 These are photos of the actual objects after edge sealing and corrosion using different methods. DETAILED DESCRIPTION

[0032] The following common laboratory tools are used in the edge sealing and sample preparation for corrosion tests: sandpaper, crucible tongs, electric hot plate, φ100mm flat-bottomed glass dish, and pointed tweezers.

[0033] The specific sample preparation method is as follows:

[0034] 1. According to the corrosion test requirements, cut the coated steel plate samples into certain sizes.

[0035] For reference, 30mm×50mm×δ(thickness) can be used. To facilitate hanging the sample, a hole is punched in the middle of the short side, or two holes are punched at equal distances at symmetrical positions on both sides of the long side. The diameter of the holes is φ3mm (see Figure 1 );

[0036] 2. Use sandpaper to remove the burrs on the punched parts, cut parts and sharp corners of the specimen;

[0037] 3. Use alcohol to clean the coating surface of the test sample. You can also refer to the GB / T19746-2018 standard to clean the sample to remove the oil on the coating surface of the sample.

[0038] 4. Before the experiment, measure from the bottom upwards on the outer wall of the flat-bottomed glass dish and mark the 5mm and 8mm lines, and place the flat-bottomed glass dish on the electric heating plate;

[0039] 5. First, put a small amount of protective material in a glass dish according to a certain ratio, turn on the electric heating plate, set the temperature to 270℃, heat it to melt and form protective liquid, and then gradually add protective material until the liquid level reaches 5mm;

[0040] 6. Use crucible tongs to clamp the center of the sample. Because the front end of the crucible tongs is hollow near the clamping part, it can avoid contact with the four sides of the sample. Before use, stick a piece of tape on each of the two clamping ends of the front of the crucible tongs to increase the stability of the clamping and avoid scratching the coating.

[0041] 7. First, perform protective treatment on the three unpunched edges of the sample. Clamp the center of the sample with crucible pliers, and immerse one side of the sample vertically into the protective liquid in the flat-bottomed glass dish for 3-5 seconds. After taking it out, the protective liquid quickly solidifies at the incision to form a flat protective film. The other two sides can be done in turn. If you need to increase the thickness of the protective film, you can repeat this step. Then protect the punched incision edge. At this time, you need to continue to add protective material until the liquid level reaches 8mm. The purpose is to immerse the hole on one side of the sample in the protective liquid, so that a protective film is formed on the incision position and the punched position on the punched side;

[0042] 8. Use pointed tweezers to expand a hole of about 2mm on the protective film at the punching position, leaving a protective layer of about 1mm for hanging the rope;

[0043] 9. Check the protective film at the cutout and opening of the sample. If the seal is intact, the test can be carried out according to the standard. This protective material can be used for full immersion corrosion test and weekly immersion corrosion test, and can meet the corrosion test requirements in the test temperature range of 20-70℃.

[0044] Industrial paraffin: It has a low melting point, usually 50-70℃. It can be used for hot dip edge sealing after being heated and melted directly. The method is simple, but it is soft, not wear-resistant and not resistant to high temperatures. It cannot meet the corrosion test conditions with temperature requirements when used alone. For example, the experimental temperature of the weekly immersion test is usually 80℃.

[0045] High-density polyethylene: high melting point, usually 130-135°C, high hardness, certain wear resistance and impact resistance, generally formed by injection molding, extrusion, etc., not suitable for edge sealing of samples;

[0046] The invention combines the advantages of the two materials and adds a certain proportion of high-density polyethylene into industrial paraffin to increase the melting point of the material and appropriately improve its hardness and wear resistance.

[0047] Melting point test:

[0048] Heat and melt the two materials in different ratios, stir them evenly, reheat them after solidification and test their melting points;

[0049] Edge sealing effect test of samples:

[0050] The two materials were heated and melted in different proportions, and experiments were conducted at different heating temperatures. When the heating temperature is too low, the melting speed of paraffin and polyethylene particles is slow, the polyethylene particles cannot be completely melted, the mixture with paraffin is uneven, and cracking is likely to occur after solidification; when the heating temperature is too high, it is easy to destroy the molecular structure of the material and cause polyethylene degradation, the surface quality deteriorates after solidification, and cracking will also occur. A series of temperature experiments were compared for the heating temperature. Table 1 lists the experimental results of different material ratios under two heating temperatures of 200℃ and 270℃.

[0051] Table 1 Comparison of protective material ratio and heating temperature

[0052]

[0053] Note: A: industrial paraffin, B: high-density polyethylene

[0054] After experimental optimization, a ratio of 60-70% industrial paraffin + 30-40% high-density polyethylene is adopted, the melting point range can be adjusted to 80-100°C, and a heating temperature of 270°C is adopted, which is more conducive to uniform mixing of the two materials. After hot-dip edge sealing, cracks are not easy to occur, causing the edge sealing to fall off, and the corrosion test with temperature requirements, such as weekly immersion test, etc., can be met. For full immersion test at room temperature, 100% industrial paraffin or 80-90% industrial paraffin + 10-20% high-density polyethylene can also be used. The effect of hot-dip edge sealing can meet the requirements of full immersion experiment at room temperature.

[0055] The technical solution focuses on the following three points:

[0056] First, the ratio of protective materials;

[0057] The second is the heating temperature;

[0058] The third is the processing of samples;

[0059] Grinding of sharp corners of specimens and cleaning of specimens.

[0060] The processed samples have sharp corners, and the sample surface is inevitably contaminated. The sharp corners need to be polished and the samples need to be cleaned. For samples without sharp corners, the protective layer at the sharp corners is thin and the sharp corners are easily damaged. This problem can be avoided after polishing; the unwashed samples will not hang on the edge during hot dip. After cleaning, the wettability is improved and the edge sealing effect is good.

[0061] Comparison with conventional edge banding methods

[0062] Laboratories generally use the tape edge sealing method. During the actual corrosion test, it was found that for the full immersion test and the weekly immersion test, the edge sealing effect did not meet the requirements. The corrosive liquid entered the tape and caused red rust on the edge, affecting the experimental results.

[0063] Example 1: Full immersion corrosion test

[0064] The method of the present invention was used to prepare the edge of a zinc-aluminum-magnesium coating sample, and the test was carried out in solutions with different pH values. Specifically, an aqueous solution containing 1 g / L of Na2SO4 was used as the basic solution, H2SO4 was added to the acidic side, and NaOH was added to the alkaline side. The pH of the test solution was 2, 4, 7, 12, and 14. After the edge of the sample was sealed, it was completely immersed in the solution for 24 hours to observe the Figure 2 , the implementation effect is good, see Figure 3 Because the coating area reacts violently with acidic solutions and hardly reacts with alkaline solutions, Figure 3 The contrast effects between the edge and the coating of the sample shown in (b) are different. The purpose of this experiment is to verify that the protective material used does not react with the test solution and has a good edge sealing effect.

[0065] Example 2: Cyclic Immersion Corrosion Test

[0066] The method of the present invention was used to prepare edge sealing samples for a coating sample, and a cyclic immersion corrosion test was performed. The specific test conditions were: a CHZJ-1200 cyclic immersion corrosion tester was used, the test solution was NaCL: 20 g / L, the test temperature was 45°C, the test humidity was 70% RH, the baking temperature was 70°C, the immersion time was 12 min, the baking time was 48 min, and the corrosion time was 120 h. The edge sealing effect was good, as shown in Figure Group 4.

[0067] Example 3: Comparison of the effects of different edge sealing methods

[0068] The effects of edge sealing and corrosion using different methods are shown in Figure 5.

[0069] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A protective material for edge sealing, characterized in that: Industrial paraffin and high-density polyethylene are mixed in a certain proportion so that the melting point ranges from 80-100°C and has a certain hardness and toughness. The material has the characteristics of not reacting with acids, alkalis and salts, and meets the requirements of edge sealing protection in corrosion tests.

2. The edge sealing protective material according to claim 1, characterized in that: The ratio of 60-70% industrial paraffin + 30-40% high-density polyethylene is adopted, the melting point range can be adjusted to 80-100℃, and the heating temperature of 270℃ is adopted, which is more conducive to the uniform mixing of the two materials. After hot-dip edge sealing, it is not easy to crack and cause the edge sealing to fall off, which meets the corrosion test requirements for temperature.

3. The edge sealing protective material according to claim 1, characterized in that: Using 100% industrial paraffin or 80-90% industrial paraffin + 10-20% high-density polyethylene, the effect of hot-dip edge sealing meets the requirements of full immersion experiment at room temperature.

4. The edge sealing protective material according to claim 1, characterized in that: The protective material can be used for full immersion corrosion test and peripheral immersion corrosion test, and meets the corrosion test requirements within the test temperature range of 20-70°C.

5. The method for preparing samples of the protective material for edge sealing according to any one of claims 1 to 4, characterized in that: The specific steps include: 1). According to the corrosion test requirements, cut the coated steel plate sample into a certain size; To facilitate hanging the specimen, punch a hole in the middle of its short side, or punch two holes at equal distances on both sides of the long side at symmetrical positions; 2) Use sandpaper to remove the burrs on the punched parts, cut parts and sharp corners of the sample; 3). Use alcohol to clean the coating surface of the test sample. You can also refer to the GB / T19746-2018 standard to clean the sample to remove the oil on the coating surface of the sample; 4). Before the experiment, measure from the bottom to the top on the outer wall of the flat-bottomed glass dish and mark the Amm position and Bmm position lines, and place the flat-bottomed glass dish on the electric heating plate; 5). First, place a small amount of the protective material in a glass dish, turn on the electric heating plate, set the temperature to 270°C, heat it to melt and form a protective liquid, and then gradually add protective material until the liquid level reaches the Amm position; 6). Use crucible tongs to clamp the center of the sample. Because the front end of the crucible tongs is hollow near the clamping part, it can avoid contact with the four sides of the sample. Before use, stick a piece of tape on each of the two clamping ends of the front of the crucible tongs to increase the stability of the clamping and avoid scratching the coating. 7). First, perform protective treatment on the three unpunched edges of the sample; clamp the center of the sample with a crucible clamp, and immerse one edge of the sample vertically into the protective liquid in the flat-bottomed glass dish for 3-5 seconds. After taking it out, the protective liquid quickly solidifies at the incision to form a flat protective film. The other two edges can be processed in turn; if the thickness of the protective film needs to be increased, this step can be repeated; then protect the punched incision edge. At this time, it is necessary to continue to add protective material until its liquid level reaches the Bmm position. The purpose is to immerse the hole on one side of the sample in the protective liquid, so that the incision position on the punched side and the punched position form a protective film; 8). Use pointed tweezers to expand a hole in the protective film at the punching position, leaving a certain protective layer for hanging the rope; 9). Check the protective film at the cutout and opening of the specimen. If they are sealed intact, the test can be carried out according to the standard.

6. The method for preparing samples of the protective material for edge sealing according to claim 5, characterized in that: The size of the coated steel plate specimen is 30 mm × 50 mm × δ thickness.

7. The method for preparing samples of the protective material for edge sealing according to claim 5, characterized in that: In the step 1), the diameter of the holes is φ3 mm.